Mesin Pencetak Pakan Ikan Alternatif Bagi Masyarakat Desa Buluhcina, Kecamatan Siak Hulu, Kabupaten Kampar - Badri, Muftil; Aziz, Azridjal; Dalil, Mohammad; Kurniawan, Iwan; Abdurrahaman, Ridwan; Kusuma, Andi Arief (Fakultas Teknik UMSU, 2023)
Buluhcina is one of the villages in Siak Hulu, Kampar District, Riau Province. The natural wealth potential in Buluhcina includes: (1) several villagers develop cage fish cultivation; (2) the river along the village as a natural potential has lots of fish needed by the community; and (3) lakes and swamps that have the potential to be developed for new jobs. From the community service activities in Buluhcina, it was concluded that: (1) this fish feed molding machine is capable of producing fish feed, the feeds is produced from the machine must be dried by conventional drying (the heat from the sun). (2) Running test for the production of fish feeds that have been made are used as samples of fish feed developed in Buluhcina. Operational training activities for produce the alternative fish feed have been successfully carried out in Buluhcina.